1996
DOI: 10.1093/ajcp/106.4.483
|View full text |Cite
|
Sign up to set email alerts
|

CD 5 Immunoreactivity of Epithelial Cells in Thymic Carcinoma and CASTLE Using Paraffin-Embedded Tissue

Abstract: Because the histologic features may resemble those of other mediastinal malignancies, thymic carcinoma can be difficult to diagnose, particularly if the primary site is uncertain. In an effort to facilitate this diagnosis, the authors have evaluated the use of immunohistochemistry with an antibody to CD5 (NCL-CD5). Nine thymic carcinomas, 15 thymomas, 8 lymphomas, 10 poorly differentiated lung carcinomas, 10 breast carcinomas, 1 mediastinal seminoma, and 1 thyroid carcinoma showing thymus-like differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
43
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 4 publications
4
43
0
Order By: Relevance
“…[28][29][30] We verified that IU-TAB-1 cell line does not express c-KIT (CD117) and EGFR markers, which are typically expressed in thymic carcinomas. 31,32 Genetic alterations in thymomas have been correlated with the histological WHO subtype and the clinical behavior.…”
Section: Discussionsupporting
confidence: 56%
“…[28][29][30] We verified that IU-TAB-1 cell line does not express c-KIT (CD117) and EGFR markers, which are typically expressed in thymic carcinomas. 31,32 Genetic alterations in thymomas have been correlated with the histological WHO subtype and the clinical behavior.…”
Section: Discussionsupporting
confidence: 56%
“…3). This peculiar cancer dissemination has been suggested for other neoplasms [14,[20][21][22], especially for pleural mesothelioma [23], but never in CASTLE disease. Taking our experience into account, prophylactic radiotherapy treatment of the area(s) submitted to fine needle aspiration could be considered and recommended in CASTLE, as was successfully adopted in mesothelioma [24].…”
Section: Discussionmentioning
confidence: 77%
“…Even if cytology shows characteristic cells (e.g., squamoid cells with eosinophilic cytoplasm, oval nuclei with small distinct nucleoli), morphology alone may not be sufficient for a diagnosis. The expression of immunohistochemical markers is in fact helpful for the correct interpretation of the samples [5,10,11,[13][14][15]. Recently, Ito et al, in reviewing 23 cases of CASTLE, showed a strong sensitivity (82%) with a specificity of one hundred percent for CD5, even if the diagnosis was already based on samples [5].…”
Section: Discussionmentioning
confidence: 99%
“…Two of these markers, c-kit and CD5, have already been shown in many publications. 4,3,7,5,9,8 Among these 'positive' thymic carcinoma markers identified in the current study, GLUT-1 may be one of the best markers for diagnosing thymic carcinoma for the following reasons. First, GLUT-1 is the marker, which showed the highest sensitivity and specificity for thymic carcinoma (Table 4).…”
Section: Discussionmentioning
confidence: 86%
“…It is sometimes difficult to make the differential diagnosis between thymoma type B3 and thymic carcinoma histologically, especially when the biopsy specimen is small. Although immunoreactivity for CD5 and c-kit has been reported as a useful marker for primary thymic carcinoma, but not for thymoma, the positive rate of CD5 and c-kit has been reported to be limited to over 50%; [3][4][5][6][7] and as not all neoplastic cells in thymic carcinomas stain positive for these markers, [8][9][10][11] it will be necessary to identify other diagnostic markers to make the differential diagnosis more reliable.…”
mentioning
confidence: 99%